Water pipeline leakage detection using vibration method - Tahwil Azar, Hazwan Azhar (2014)
Water leakage is a common problem that often results in water waste, damages, and hazards to public health. Existing leak detection tools and methods typically rely only one sensor to detect and pinpoint leaks, therefore the leakage is not identified until the water has risen above the surface. This project addresses this shortcoming by developing a prototype system that is fed with multi-sensor fusion data from flow rate and pressure sensors and accelerometers. This project proposed a new method in detecting water pipeline leakage with vibration method using accelerometers in which it is low cost and can detect leakage correctly. The connections between both accelerometers and the laptop are through serial/wired communications. Results show that the prototype model can detect the leakage in the water pipeline system. However it has a distance range in which it can detect the leakage. This is the disadvantage of using this method which can be overcome in future research. Future development will focus on testing the prototype system with various parameters such as pipe diameter and materials in the real environment using wireless networks to transfer data between sensors and prototype model system.